ANMCO POSITION PAPER: The management of suspect or confirmed COVID-19 patients needing urgent electrophysiology and/or electrostimulation procedures. (27th August 2020) - Gulizia, Michele Massimo; Zecchin, Massimo; Colivicchi, Furio; Francese, Giuseppina Maura; Murrone, Adriano; Caldarola, Pasquale; Di Lenarda, Andrea; Valente, Serafina; Roncon, Loris; Amodeo, Enzo; Aspromonte, Nadia; Cipriani, Manlio Gianni; et al.
Abstract: The aim of this document is the management and organization of patients in need of urgent access to electrophysiology (EP) and pacing procedures during the COVID-19 emergency. Specifically, non-deferrable procedures or irreplaceable with a drug therapy prior to the resolution of the COVID-19 virus emergency [pacemaker (PM) implant/replacement/urgent defibrillator (implantable cardioverter-defibrillator, ICD) or arrhythmic storm or other indication of non-deferrable ablation]. The pacing and electrophysiological procedures urgent as they may be, less and less frequently represent situations of emergency, therefore for almost all cases, it is possible to perform a swab test to determine the positivity to COVID-19 of the patient. In cases where this is not possible, due to situations of emergency, the recommendations and procedures we have indicated are advisable, if not mandatory, in order to avoid the spreading of the virus to healthcare personnel and other patients.